2020
DOI: 10.1017/s0266462320000409
|View full text |Cite
|
Sign up to set email alerts
|

Quality of economic evaluations of ventricular assist devices: A systematic review

Abstract: Objective Because of a lack of suitable heart donors, alternatives to transplantation are required. These alternatives can have high costs. The aim of this study was to perform a systematic review of cost-effectiveness studies of ventricular assist devices (VADs) and to assess the level of evidence of relevant studies. The purpose was not to present economic findings. Methods A systematic review was performed using four electronic databases to identify health economic evaluation studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In line with the present study, some performed systematic reviews of HEEs examining reporting quality in the fields of cardiology, neurology, plastic surgery, and artificial intelligence in healthcare. [19][20][21][22] Some of them also reported adherence to each item of CHEERS 2013, and similar trends, e.g., insufficient reporting in the Methods section, such as the study by Tai et al, were observed. 20,21 All of these studies commonly used CHEERS 2013; however, they share common features.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In line with the present study, some performed systematic reviews of HEEs examining reporting quality in the fields of cardiology, neurology, plastic surgery, and artificial intelligence in healthcare. [19][20][21][22] Some of them also reported adherence to each item of CHEERS 2013, and similar trends, e.g., insufficient reporting in the Methods section, such as the study by Tai et al, were observed. 20,21 All of these studies commonly used CHEERS 2013; however, they share common features.…”
Section: Discussionmentioning
confidence: 65%
“…17 To date, the CHEERS statement has been reported in several systematic reviews of HEE studies or in those focusing on the quality of reporting in HEE research. [18][19][20][21][22] However, most studies have used it as a scoring tool, which is stated in the standards as misuse of the tool, 15 or in the context of assessing methodological quality, resulting in few accurate assessments of reporting transparency. Furthermore, there is only one previous systematic review of HEEs of ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned methodology of combining several checklists was based on previous work on the quality of economic evaluations (16;17). To our knowledge, no single checklist exists that is able to measure both the reporting and the methodological quality of economic evaluations.…”
Section: Methodsmentioning
confidence: 99%